المؤسسة الاقتصادية ومدى تحسين صورتها لدى الجمهور الداخلي والخارجي - بلقلعي, اسماء (My University, 2020)
Abstract : With the developement of economy and the emergence of competing institutions in the market , it has become necessary that institutions take care of their mental picture, make them one of their priorities, and srtive to win and preserve them. Thus, our study revolves around the economic institution and extent to improve its image among the internal and external audience. Study of the National Electricity and Gaz Distribution Company _Directorate of Distribution, Mostaganem, where we presented the following problem how the economic institution contributes to improving its image among the internal and external audience ? We relied on the case study method, so we took the Sonelgaz foundation as a model, we have also relied on the sample it consiste of five (05) vocabulary words for both the internal and external audience, consideratness to the current health situation. As for the tool, we relied on the interviewer as it a direct tool and helps us to go deeper into our research this, after formulating the problem and defining the method, maintenance and tool, we discussed the theoretical side, which include two chapters. The first chapter which is an introduction to the concept of mental image, in which we dealt with the definition of mental image, , we also studied the basics of mental image, We also covered the organization’s imageinstitution and its concepts, where we dealt with concepts about the economic institution, then we discussed the types of economic institutions, its goals, its functions and its rules. Also we dealt with the transformations experienced by Algerian institutions in light of the market economy. As for the practical aspect, we have divided the interview guide into two parts : An interview guide for the internal audience which includes three tracks, and an interview guide for the external audience, which included four axes. And the study was based on results, including the fact that the Algerian Electricity and Gaz Distribution Company, Directorate of Distribution, Mostaganem, has a wide knoweledge of its external audience. And this is what the internal public of the institution stated, including workers and empolyees, where they affirmed that the institution is striving to strengthen the relationship and permanent closeness to the customer by providing communication mechanisms ( phone number, website, Agencies, etc…). Also the confidence of the external public in the institution is shown by the large increase on the number of customers, but the outside public had a different opinion of their confidence in the institution, so that he is ignorant of them as unworthy services, this is what the first hypothesis reached, represented by «the Algerian Electricity and Gaz Distribution Directorate is distiguished by a wide knowledge among its public », as it is considered a completely incorrect hypothesis, where we notice that there is a contradiction between the internal and external audiences, and this is through the observations and interviews we carried out with the institution’s empolyees and customers. The second hypothesis from which we concluded that the Algerian Electricity and Gaz Distribution Company_ Directorate Mostaganem, it relies on modern and traditional means and techniques to improve its picture among its external audience, represented by the open doors, field out put, advertising, Radio, TV, Press interviews, Newspapers and publications, so that these activites are considered an effective communication strategy to improve the image of the institution, but the external audience has no idea about that activities, and they emphasized that the institution is self_contained and does not advertise in order to inform citizens of its services, it also laks the slightest strategy to deal with the customer, consequentely, the second hypothesis represented by the Algerian corporation for Electricity and Gaz distribution that « Mostaganem relies on traditional and modern means and techniques to improve its image with its external audience» is correct, where the institution relies on various means, to improve its picture, as for the audience, it doesn’t have the instituion’s culture, accers to its developements and interaction with it, depending on the image of economic institution can be improved by good and respectfull dealings, and also trying to implement electronic management, and this is what the outside public stated that electronic management helps Sonelgaz foundation to facilitate customer service and communication with him and this matte is gradually, thus, this is assumption that electronic management contributes to improving the image of the economic institution and helps it to deal with the customer is correct, however, it cannot be generalized to all customers, but to the conscious category that has a culture of electonic management and remote communication, thus, we conclude that the mental picture is one of the institution’s priorities, whether it is economic or serviceable, it is an essential pillar for the internal audience to work to gain and preserve. Sonelgaz is working to improve its image and give a good reputation, as well as working to provide an worthy service to the customer. institution’s services and describes it as a monopoly in the market, and that citizen must resort to it and deal with it ; Thus, the outside public remains dissatisfied with the services of Sonelgaz, and sees management. We also touched on the second chapter to economic
Keywords: المؤسسة الاقتصادية،تحسين صورة المؤسسة ،الجمهور الداخلي والخارجي